Training needs and curriculum of continuing medical education among general practitioners in Tibet, China: A cross-sectional survey - An, Kang; Zhang, Lin; Qiao, Runjuan; Li, Caizheng; Zhong, Qian; Ma, Yiru; Rao, Xin; Mao, Tingrui; Liu, Feng; Zhuo, Qiang; She, Yi; Li, Shuangqing; et al. (Frontiers in Public Health, 2022)
Background: Inequalities in health resources are higher in Tibet than in other regions. The development of core professional capability for general practitioners (GPs) is the main goal of continuing medical education (CME) training program. Aim: This study aims to explore the needs of CME for GPs and provide advice for the development of policy, practice, and CME curriculums. Methods: We conducted a cross-sectional online survey among GPs in Tibet Autonomous Region, China. We designed an online questionnaire including the demographic section, training contents, and training formats about CME. Results: A total of 108 questionnaires were included in this study. 79 (73.15%) were female. 56 participants (51.85%) were working in primary care settings. We developed a curriculum priority: first-choice, major alternatives, and secondary considerations. The topics identified as first-choice for CME were related to “cardiovascular disease” (85.19%), “respiratory disease” (81.48%), and “digestive disease” (80.56%). Major alternatives included two essential knowledge and eight clinical skills items. We rated ten items as secondary considerations. Only 39.81% ranked mental health as an essential priority; bedside teaching (51.85%) was the first choice. Conclusion: We presented priority areas identified in this study to focus on CME for GPs in Tibet. The 23 topics may reflect the features of general practice, which increasingly require common disease management skills, while demand-oriented curriculum and staged training plans should be adopted. CME programs should be adapted dynamically to respond to evolving needs. Keywords: continuing medical education; primary care; curriculum development; training needs; general practice